Becoming wise [compact disc, unabridged] : an inquiry into the mystery and the art of living - Tippett, Krista (Penguin Audio, 2016)
Offers guidance on the art of living drawn from the stories of extraordinary people whose work inspires wonder and insight into life, finding common ground between a wide variety of thinkers on how to be present in the world.